Beyond Neighborhood Socioeconomic Status: Exploring the Role of Neighborhood Resources for Preschool Classroom Quality and Early Childhood Development. Issue 3 (29th March 2021) - Wei, Wendy S.; McCoy, Dana C.; Busby, Andrea Kinghorn; Hanno, Emily C.; Sabol, Terri J.
Abstract: The neighborhood literature consistently documents associations between neighborhood socioeconomic status (SES) and child development. Yet, this approach may miss important heterogeneity in neighborhood resources (e.g., libraries, doctors' offices) that have important implications for children. Moreover, the mechanisms that explain the relation between neighborhood characteristics and child outcomes are poorly understood. Using a sample of 955 children situated in preschool neighborhoods across nine United States cities, the present study aimed to (1) describe the relation between neighborhood SES and resources among our sample neighborhoods and (2) explore whether neighborhood SES and resources may be (a) independently and (b) jointly associated with young children's gains in language/literacy and executive function skills via differences in preschool classroom process quality. Our results suggested that neighborhoods were heterogeneous in both SES and resources, thereby indicating a diverse range of resource availability among lower SES neighborhoods. Moreover, we found that both neighborhood SES and resources were individually associated with benefits to children's development through levels of classroom process quality and that these associations were magnified in communities that were particularly high in both SES and resources. These findings point to potential policy levers at both neighborhood and classroom levels to support children's development. Highlights: Neighborhoods in nine US cities exhibit heterogeneity in socioeconomic status (SES) and resources. Classroom instructional support is one mechanism through which neighborhoods matter for development. Neighborhood resources matter for child development via levels of classroom quality. Instructional quality is highest in neighborhoods with higher levels of both SES and resources.